Brand Awareness dan Pengaruhnya terhadap Keputusan Pembelian Peralatan Outdoor Lokal - Ahmad Ibrahim; Oktaviana Purnamasari (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines the influence of Arei Outdoor Gear brand awareness on purchase decisions in the Bogor Climbing Virtual Community on Facebook. In the midst of increasingly fierce competition in the outdoor equipment industry, maintaining a high level of brand awareness is an important factor for companies in attracting and retaining consumers. Therefore, this study aims to find out the extent to which brand awareness of Arei products is able to influence the purchasing decisions of the community members. This study uses a quantitative approach with a survey method conducted on 87 respondents who were randomly selected from community members. Data collection was carried out through a questionnaire which was then analyzed using a simple linear regression technique to determine the relationship between brand awareness variables and purchase decisions. The results of the study show that the level of Arei brand awareness is relatively high with an average value of 3, where respondents are able to recognize Arei's products, logos, and brand characteristics. Meanwhile, purchasing decisions are also in the positive category with an average score of 3.25. The results of linear regression analysis showed a significant influence between brand awareness on purchase decisions with a correlation value (R) of 0.749. In addition, a determination coefficient value (R²) of 0.561 showed that 56.1% of purchase decisions were influenced by brand awareness, while the rest were influenced by other factors outside of the variables studied.